Metafore iz grško-rimskega sveta v delih slovenskega pisatelja Alojza Rebule - Cergol, Jadranka (Slavia Centralis, 2020)
Metaphors from the Graeco-Roman World in the Works of the Slovene Writer Alojz Rebula The paper presents a detailed analysis of certain similes and metaphors in the works of the Slovene writer Alojz Rebula, focusing mainly on the metaphors that have Graeco-Roman similes as their subject. Based on the interaction theory of metaphor the author first presents classical antiquity as the primary subject, and later on as the secondary subject. The last part of the paper focuses entirely on the meaning of interaction in the literary works of Alojz Rebula.